2020
DOI: 10.1155/2020/7380740
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Carbapenemase-Encoding Genes in Multidrug-Resistant Acinetobacter baumannii Clinical Isolates in South Africa

Abstract: Introduction. Carbapenem-resistant Acinetobacter baumannii has been responsible for an increasing number of hospital-acquired infections globally. The study investigated the prevalence of carbapenemase-encoding genes in clinical multidrug-resistant A. baumannii strains. Materials and Methods. A total of 100 nonduplicate multidrug-resistant A. baumannii strains were cultured from clinical samples obtained from healthcare facilities in the O. R. Tambo district. The strains were confirmed by detecting the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(38 reference statements)
4
17
0
Order By: Relevance
“…is study results reveal a high resistance to most of available antibiotics used by clinicians in management of A. baumannii infections (cefotaxime 89%, ceftazidime 85%, cefepime 85%, piperacillin + tazobactam 76%, imipenem 83%, meropenem 83%, ciprofloxacin 83%, gentamycin 81%, and trimethoprim-sulfamethoxazole 82%) (Figure 1). e findings are similar to several reports made by different researchers within the region [54][55][56] and globally [58]. In their published report on the district of Oliver Reginald Tambo in the Eastern Cape Province of South Africa, Anane et al [55] highlighted that A. baumannii strains showed resistance rates above 80% against the same antibiotics tested in this current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…is study results reveal a high resistance to most of available antibiotics used by clinicians in management of A. baumannii infections (cefotaxime 89%, ceftazidime 85%, cefepime 85%, piperacillin + tazobactam 76%, imipenem 83%, meropenem 83%, ciprofloxacin 83%, gentamycin 81%, and trimethoprim-sulfamethoxazole 82%) (Figure 1). e findings are similar to several reports made by different researchers within the region [54][55][56] and globally [58]. In their published report on the district of Oliver Reginald Tambo in the Eastern Cape Province of South Africa, Anane et al [55] highlighted that A. baumannii strains showed resistance rates above 80% against the same antibiotics tested in this current study.…”
Section: Discussionsupporting
confidence: 92%
“…e findings are similar to several reports made by different researchers within the region [54][55][56] and globally [58]. In their published report on the district of Oliver Reginald Tambo in the Eastern Cape Province of South Africa, Anane et al [55] highlighted that A. baumannii strains showed resistance rates above 80% against the same antibiotics tested in this current study. Similarly, Lowe et al [57] in Tshwane district in Gauteng province of South Africa reported high prevalence of resistance (69-90%) of A. baumannii strains to the same antibiotics tested in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[32][33][34][35] Overexpression of OXA-51 and OXA-23 has been associated with insertion (IS) elements located upstream of their gene. [36][37][38] One of the most common IS elements is the ISAba1, which promotes the expression of these genes and modifies their mobility. 37 Numerous studies reported that A. baumannii isolates bearing ISAba1, especially upstream bla OX A-51…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on the increased incidences and propagation of carbapenem-resistant A. baumannii (CRAB) across continents in the last few years have received physicians’ attention. Carbapenem resistance is a severe problem affecting Africa’s health-care system, where the occurrences have surged from <1 to 60% among Gram-negative bacteria ( Anane et al, 2020 ). In a recent study carried out in Nepal’s tertiary care hospital, of the 177 A. baumannii studied, nearly 91% of them exhibited carbapenem resistance ( Devkota et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%